Dopo la morte dell'io Percorsi bassaniani «di là dal cuore» - Dolfi, Anna (Moderna/Comparata, 2017)
The death of the self passes through modern culture. However, chooses for himself the role of Psychopomp in obeyance not only to stylistic but also to profoundly ethical reasons. Bassani interrupts his narrative writing to give unity to the Romanzo di Ferrara and to entrust poetry with verses in the form of an epitaph. The testimonial "need" seems to emerge, giving meaning through the Prologue to the Giardino dei Finzi-Contini and to what will come after. It seems that the coherent constructive geometry of an entire work (intertwined since the beginning with refined European readings, figurative and Longhiani memories that Anna Dolfi highlights with wise precision) fully reveals the excess of the hourglass shape, of the conical structures that allow to glimpse distant flakes of light, pushing the real on the perilitant discrimination of the shadow. There, where the existing (objects, characters / people) is offered as a painted image alive only thanks to refraction and indirect projection of the gaze. This book investigates the strategies of Bassani's memory and his playing on revelation / concealment, while deeply analysing the compositional paths of the texts in their allocative ways (the very privilege, in poetry, of the dialogic and epistolary form). Moreover, the work strongly questions the places of the distance, the introjection of mourning, the relationship between history and truth, between the code of reality and the effect of reality, the convergences between biography and culture (in the names of Caravaggio, Cézanne, De Staël, Morandi, Bacon; Dante, Manzoni , Tommaseo, Hawthorne, James, Dickinson, Baudelaire, Mallarmé, Rimbaud ...), offering a new and suggestive interpretation of Bassani's "writing beyond the heart".